Match-related statistics discriminating between playing positions during the men's 2011 Rugby World Cup - Villarejo, D.; Palao, J.-M.; Ortega, E.; Gomez-Ruano, M.-A.; Kraak, W. (International Journal of Performance Analysis in Sport, 2015)
The aim of the study was to investigate and compare the match-related statistics for the different playing positions based on the match outcome during the men's 2011 Rugby World Cup. A total of 48 matches from the men's 2011 Rugby World Cup were used for the purpose of this study. The performance indicators were divided into two groups based on the principles of play: attack and defence. Univariate (t-test) and multivariate (discriminant) analyses of data were done. The results demonstrated performance indicators that measure positive aspects of performance (kicks executed, tries, try assists, runs executed, kick return runs, metres gained per run, line breaks, and offload) as well as negative aspects (pick up and drives, tackles executed, ineffective tackles and missed tackles) which discriminate the final outcome regarding playing positions. This paper discusses the characteristics of each playing position regarding their game actions and their incidence in the game. The results and evaluations obtained in the present study can serve as a guide or criteria to take into consideration when training as well as in the research field of rugby with regard to game patterns.